The Effectiveness of Implication in New Formulations of the Contemporary Industrial Product: زياد حاتم حربي (Al-Academy, 2019)
The current research aims at transforming the concept of implication from the rhetoric into the industrial design in order to have a new term (the design implication) in which the industrial designer takes all or part of another's design to imply his design in it and acknowledge that, and if he did not do so, it would be (design theft) parallel to the literary plagiarism. In order to show the potentials of the industrial design in the production of new formulations of the industrial products forms, as the design is the carrier of language that addresses the recipients, it is possible to use the implication as a the tool of literature in the design and as a design strategy as it is one of the concepts that takes its course in establishing a new formulation of the industrial product, the research has identified its problem by the following question: (How does the concept of implication work as a strategy in a new formulation of the contemporary industrial product?) The aim of the research is to reveal the concept of implication as a design strategy in general and its patterns in particular. The research is divided into three sections and the first of which was entitled the implication in language and design, while the second focused on implication in the design system of the industrial product. The third section was entitled the implication and the new formulations in the contemporary industrial product